Molecularly imprinted polymer for extraction of patulin in apple juice samples. (December 2016) - Anene, Amira; Hosni, Karim; Chevalier, Yves; Kalfat, Rafik; Hbaieb, Souhaira
Abstract: A new molecularly imprinted polymer (MIP) was prepared in a two-step process. First, SiO2 -γ-MPTS was obtained by mixing γ-methacryloxypropyltrimethoxysilane (γ-MPTS) and tetraethoxysilane (TEOS). Second, SiO2 -γ-MPTS was polymerized in the presence of patulin (PAT) as a template, maleic acid (MA) as a functional monomer, ethylene glycol dimethacrylate (EGDMA) as a cross linker, 2, 2-azobis- (2- methylpropionitrile) (AIBN) as a precursor and acetonitrile as a porogen solvent. The prepared sorbent was successfully applied to selective solid phase extraction (SPE) of PAT in containing apple juices and the MIP@SPE method was validated. The optimum conditions for PAT extraction using the novel MIP@SPE were: 50 mg mass of adsorbent, sodium bicarbonate with (1%) acetic acid as washing solvent and 5 mL acetonitrile as eluting solvent. The developed MIP@SPE method had high selectivity and good affinity toward PAT and the recoveries of the target analyte were in the range of 82–98% with a precision of 3.03%–3.83% (RSD). In addition, a good linearity ( r 2  > 0.99) within the range 0.1–10 mg L −1 and a low LOD (8.6 μg L −1 ) and LOQ (28.6 μg L −1 ) were obtained. The test of reusability showed good results for at least 6 cycles. Highlights: Development of novel MIP@SPE procedure for extraction of Patulin toxin. High selectivity and good affinity of MIP@SPE method toward Patulin. Establishment of performance characteristics for developed method by single laboratory validation. Successful application of MIP@SPE procedure for determination of patulin in commercial apple juice samples.